(x-3)(x+3)(x^2+9)(x^4+81)(x^8+3^8)=x^16-3^16
albatran:
asa este!
Răspunsuri la întrebare
Răspuns de
2
(x-3)(x+3)(x^2+9)(x^4+81)=
(a-b)(a+b)=a^2-b^2
(x^2-9)(x^2+9)(x^4+81)=
(x^4-81)(x^4+81)=
x^16-81^2
x^16-9^2^2
x^16-9^4
x^16-3^2^4
x^16-3^8
Răspuns de
1
=> (x^2-9)(x^2-9)(x^4+81)(x^8+3^8)=x^16-3^16
=> (x^4-81)(x^4+81)(x^8+3^8)=x^16-3^16
=> (x^8-3^8)(x^8+3^8)=x^16-3^16
=> x^16-3^16= x^16-3^16 ADEVARAT
Sper ca e bine
Alte întrebări interesante
Matematică,
8 ani în urmă
Limba română,
8 ani în urmă
Engleza,
8 ani în urmă
Engleza,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă